Numerical Study Mixed Convection in a Channel with an Open Cavity Involving Rotary Cylinder - Mohammed, Eman G.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2022)
A numerical study of mixed convection inside a horizontal channel with an open square cavity that includes an adiabatic rotating cylinder. The bottom wall of the cavity is heated at a constant temperature, and the remaining walls are adiabatic. The flow is incompressible, laminar and steady state. The equations of continuity, momentum and energy are solved numerically using computational fluid dynamics (CFD) with the commercial software package FLUENT 2019 R1. Reynolds number values of 50, 100 and 150, the Richardson number (0.1 ≤ Ri ≤ 10) and the angular velocity ( ω ) of cylinder is (0.5 ≤ ω ≤ 4) rad/sec with direction counter clockwise. Prandtl number for air flow is ( Pr = 0.7). The results are presented in terms of streamlines, isotherms, and the average Nusselt value is given over the heated bottom cavity. The combined effects of natural and forced convection in and out of the cavity were obtained. The results showed that at low Richardson values, Ri = 0.1 the effect of buoyancy force is neglected. The effect of increasing the cylinder speed is clearly noticeable at low Reynolds values, Re = 50. Average Nusselt values increase with increasing rotational speed of the cylinder for all Richardson values.